2019
DOI: 10.5326/jaaha-ms-6933
|View full text |Cite
|
Sign up to set email alerts
|

2019 AAHA Dental Care Guidelines for Dogs and Cats*

Abstract: The 2019 AAHA Dental Care Guidelines for Dogs and Cats outline a comprehensive approach to support companion animal practices in improving the oral health and often, the quality of life of their canine and feline patients. The guidelines are an update of the 2013 AAHA Dental Care Guidelines for Dogs and Cats. A photographically illustrated, 12-step protocol describes the essential steps in an oral health assessment, dental cleaning, and periodontal therapy. Recommendations are given for general anesthesia, pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
109
0
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(138 citation statements)
references
References 51 publications
0
109
0
15
Order By: Relevance
“…Oral disease is often observed in veterinary medicine (1). Our laboratory revealed that cats with severe oral disease requiring multiple tooth extractions had specific pain-induced behaviors, higher pain scores, changes in serum inflammatory cytokines, and lower food intake when compared with cats with no/minimal oral disease (2,3).…”
Section: Introductionmentioning
confidence: 83%
“…Oral disease is often observed in veterinary medicine (1). Our laboratory revealed that cats with severe oral disease requiring multiple tooth extractions had specific pain-induced behaviors, higher pain scores, changes in serum inflammatory cytokines, and lower food intake when compared with cats with no/minimal oral disease (2,3).…”
Section: Introductionmentioning
confidence: 83%
“…An additional motivation to investigate the prevalence of dental and non-dental disease in red foxes in Lithuania is to explore an association between dental disease and overall systemic health (Bellows et al 2019). Affected animals with dental problems demonstrate changes in diet selectivity, behaviour, and often decrease food intake (Andrade et al 2015).…”
Section: Dental and Skull Bone Pathologies Of The Red Fox (Vulpes Vulmentioning
confidence: 99%
“…The study conformed to American Animal Hospital Association Guidelines for Dental Care. [12] Client consent forms were discussed and signed. Prospectively, the University of California, Davis IACUC counseled that since samples were obtained as part of dental treatment, an IACUC protocol was not required.…”
Section: Ethical Statementmentioning
confidence: 99%